Exploring the Relationship Between Parental Involvement, Paper Folding Skills, and Early Spatial Ability: A Mediation Model - Wu, Dandan; Sun, Jin (Frontiers in Psychology, 2020)
Folding paper is a common activity in East Asian kindergartens, but its potential value to early spatial skills have not been empirically explored. This study aims to investigate whether and how paper folding skills can predict spatial ability in the early years. Altogether 101 preschoolers (Ngirl = 45, Mage = 4.54, SD = .75) were randomly sampled from two Hong Kong kindergartens and invited to complete the map-use and the paper folding tasks. The paper folding task taps two levels of children’s paper-folding skills: Basic Folding Skill (BFS) and Advanced Folding Skill (AFS). The parents reported the demographic information and their involvement in spatial activities at home. The results indicated: (1) there was significant age-related increase in the paper folding performance; (2) child age could significantly predict both BFS (β = .551, p < .001) and AFS (β = .627, p < .001), while parental involvement could only predict BFS (β = .246, p < .001); (3) after controlling for confounders, paper folding skills could significantly predict spatial ability as measured by the map-use task; (4) BFS was found to mediate the relationship between parental involvement and spatial ability. The educational implications of these findings are also discussed.